UJI FLYPAPER EFFECT TERHADAP BELANJA DAERAH PROVINSI JAWA TIMUR TAHUN 2019-2024 - lailatul hasanah; lucky Rachmawati (Jurnal Ekonomika : INDEPENDEN, 2026)
The purpose of this study is to analyze the basic economic sector, classify the regional spending and the phenomena flypaper effect of city/district government in East Java for a 6 year period from 2019-2024. The method used is to use panel data regression financial and asset management office in 38 cities in East Java province. The result of the research based on the panel data regression is Partially, PAD, DAU, and DAK have a positive and significant effect on Regional Expenditure. However, the Revenue Sharing Fund (DBH) proved to be insignificant due to allocation disparities between regions. leading to the conclusion that the flypaper effect phenomenon does not occur in East Java Province.